MONITORING & ASSESSMENT OF N2O, NOX EMISSIONS FROM FERTILIZER PLANT (NITRIC ACID) FOR THE ENVIRONMENTAL SUSTAINABILTY (Pakistan Journal of Science, 2022)
Nitrous oxide (N2O) is an invisible product of nitric acid by Ostwald process. Formed during oxidation of ammonia over platinum / Rhodium gauzes; there is a need for technology to reduce the release of nitrous oxide from nitric acid plants.N2O technology can play a major role in reducing greenhouse gas emissions. The major impact of N2O on the environment such as greenhouse gas and stratospheric ozone depletory, primary options environmentally uncontroversial materials with a long operating lifetime.Secondary controls EnviNOx does not interact in any way with the plant product or its precursors.The higher Applications in other kinds of industrial waste gas streams are also being developed. Selected catalytic Regeneration (SCR) is a well-known technology for controlling the release of nitrogen oxide (NOx) emitted by fire from various energy / chemical plants. This strategy requires a reducing agent such as ammonia to reduce NOx.This research is based directly on Practical/technical control and aims to obtain, update researchers' information on the various aspects of the Clean Development Mechanism to gain N2O emissions are reduced by ∼98–99% and higher, while NOX emission levels of 1 to ∼40 ppm are achieved. The results of ongoing investigations are promising.
Keywords: Exhaust Fume Cleaning; Selective CDM; Catalytic filter medium; NO/N2O Conversion; ENViNOx/N2O